EFFECT OF FISH DENSITY AND FEEDING RATES ON GROWTH AND FOOD CONVERSION OF GILTHEAD SEABREAM (SPARUS AURATA LINNAEUS, 1758) - Taher, M. M. (Iraqi Journal of Aquaculture, 2022)
The effect of fish density and feeding rates on growth and food conversion of gilthead seabream (Sparus aurata) was studied in floating cages and fiberglass tanks in Sammaliah Island- Abu Dhabi. The results of floating cages experiment showed that there was no significant effects (p>0.) of fish density on growth and food conversion rate but there are significant effects (p<0.05) on fish production (4.11, 7.47 and 10.08) kg/m3 for densities (50,100 and 150) fish/m3 respectively. No significant differences between weight ranges [(27-125), (21-142), (30-126)] g of these fish at the end of experiment, and also between final weights (82.3, 77.4, 67.2) g for densities (50,100,150) fish/m3 respectively. The results of fiberglass tanks experiment showed that there are no significant effects of feeding rate on growth, while there are significant effects on the food conversion rate (1.43, 2.86 and 3.71) for feeding rates (5, 7.5 and 10)% of fish weight respectively. Floating cages give better results from fiberglass tanks (growth rate 0.64 g/day compared with 0.4 g/day, final production 7.31 kg/m3 compared with 4.58 kg/m3 and final weight 75.6 g compared with 45.8 g).